Comparative investigation on the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose - Manikandan, Marimuthu; Arjunan, Ayyappan; Prabu, Marimuthu; Raja, Thirumalaiswamy; Sangeetha, Palanivelu (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Hydrotalcites (HT) have a broad spectrum of applications as prosperous heterogeneous catalysts for diverse chemical transformations. The catalytic activity of HT-based materials can be tailored by introducing siliceous material into the internal or external framework. The surface modification of the HT framework with silica mesostructures leads to the formation of versatile Lewis base, Bronsted base and redox catalytic active sites. This work presents the comparative evaluation of the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose using 1-butanol as a solvent. The composites with different external morphology were prepared by a modified template-assisted hydrothermal method, using different HT to SBA-15 proportions. The textural and morphological characterization results conferred the efficiency of the employed post-synthetic intercalation strategy to achieve the successful formation of HT/SBA-15 and SBA-15/HT composites. With optimal HT loading and surface basicity, the HTS-3 composite demonstrated the highest catalytic performance, resulting in good glucose conversions (54 %) with improved selectivity (>83 %). The observed high reactivity could be mainly attributed to the extensive dispersion of HT particles on the SBA-15 component, which contributes to a significant increase in textural properties and surface basicity. Furthermore, special attention is devoted to addressing such reactivity phenomena as active site selectivity, catalyst multifunctionality and multisite reactivity commonly encountered in mesoporous catalysis.
Keywords: composites; glucose; hydrotalcite; isomerization; SBA-15